Leadership distribution in government secondary schools in Nigeria: fact or fiction? - Imoni, Raphael Isibor (2018)
There are established notions about the importance of distributed leadership in school leadership practice. Theory and research on this currently popular leadership model mostly emanate from western contexts, notably Australia, UK and the USA. It has been portrayed as an emergent model, with professionals choosing to initiate leadership in schools and classrooms. It is closely linked to teacher leadership, because distribution invariably involves teachers. This thesis focuses on leadership practice in selected secondary schools in Nigeria, from a distributed perspective. It is based on research in Edo state, using a multiple case study design. Nigeria has a centralised education system and schools tend to have a typical hierarchical structure. This raises the question about whether and how distributed leadership can operate in such a hierarchical context. The findings show that distribution occurs in the four case study schools but that it is largely allocative, rather than emergent, with school principals allocating tasks and, to a lesser extent, roles, to teachers and leaders. The case studies indicate that hierarchical distribution of school leadership can be accomplished through such allocative distributed leadership, with distribution occurring to those who occupy both formal and informal leadership roles. The research raises questions about the differences between this mode of distribution and established notions of delegation and explores this distinction. The thesis examines a globally significant leadership model and applies it to the under-published context of Nigerian secondary schools. The research is likely to be relevant to other centralised systems considering whether and how to adapt their leadership and management practice.